Influence of splices on the stability behaviour of columns and frames - Simão, Pedro D. (2010)
The paper presents a study on the influence of splice connections on the stability behaviour of compressed steel columns. The column is modelled as two independent prismatic parts connected by a rotational spring at the splice location and rotational and extensional springs at the column ends to represent the effect of the adjacent structure. The general behaviour is characterized using a polynomial Rayleigh-Ritz approximation substituted into the potential energy function, in combination with the Lagrange’s method of undetermined multipliers, and based on this model the critical load is found. The load-carrying capacity is analysed with respect to the following variables: (i) location and rotational stiffness of the splice, (ii) change in the column section serial size and (iii) column end-restraints stiffness coefficients. A nonlinear regression model is developed to predict simple relationships between the critical load and the relevant column characteristics.